The Effect of Leverage, Financial Distress, and Transfer Pricing on Tax Avoidance (Empirical Study on Energy Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2018–2022 Period) - Seffi Aulia Dinda Pratiwi; Fauzan Fauzan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research explores how leverage, financial distress, and transfer pricing influence tax avoidance within energy sector manufacturing firms listed on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2022. The energy sector in Indonesia is particularly relevant due to its significant role in the national economy, characterized by complex regulatory environments, high capital requirements, and tax incentives that may encourage aggressive tax avoidance strategies. The study applies multiple linear regression analysis to assess the impact of these independent variables on tax avoidance. It controls for potential confounding factors such as firm size, profitability, and ownership structure to ensure the robustness of the results. The findings reveal that leverage has a significant impact on tax avoidance, while financial distress and transfer pricing do not demonstrate a notable effect. This study also considers the potential influence of regulatory changes and economic events during the study period, including tax reforms and shifts in government policies that may have affected tax behavior. The results indicate that leverage plays an essential role in shaping tax avoidance strategies, whereas financial distress and transfer pricing do not directly affect tax avoidance behaviors in the context of energy sector companies during the specified period. This research emphasizes the critical role of leverage in influencing tax avoidance practices and highlights the unique characteristics of the Indonesian energy sector that shape corporate tax behaviors.